Dual glucagon‐like peptide‐1 receptor/glucagon receptor agonist SAR425899 improves beta‐cell function in type 2 diabetes. Issue 4 (22nd December 2019) - Visentin, Roberto; Schiavon, Michele; Göbel, Britta; Riz, Michela; Cobelli, Claudio; Klabunde, Thomas; Dalla Man, Chiara
Abstract: Aim: To evaluate the change in insulin sensitivity, β‐cell function and glucose absorption after 28 days of treatment with high and low doses of SAR425899, a novel dual glucagon‐like peptide‐1 receptor/glucagon receptor agonist, versus placebo. Materials and Methods: Thirty‐six overweight to obese subjects with type 2 diabetes were randomized to receive daily subcutaneous administrations of low‐dose SAR425899 (0.03, 0.06 and 0.09 mg) and high‐dose SAR425899 (0.06, 0.12 and 0.18 mg) or placebo for 28 days; dose escalation occurred after days 7 and 14. Mixed meal tolerance tests were conducted before treatment (day −1) and on days 1 and 28. Oral glucose and C‐peptide minimal models were used to quantify metabolic indices of insulin sensitivity, β‐cell responsiveness and glucose absorption. Results: With low‐dose SAR425899, high‐dose SAR425899 and placebo, β‐cell function from day −1 to day 28 increased by 163%, 95% and 23%, respectively. The change in area under the curve for the rate of meal glucose appearance between 0 and 120 minutes was −32%, −20% and 8%, respectively. Conclusions: After 28 days of treatment, SAR425899 improved postprandial glucose control by significantly enhancing β‐cell function and slowing glucose absorption rate.